2019
DOI: 10.1088/1742-6596/1387/1/012115
|View full text |Cite
|
Sign up to set email alerts
|

Application of Technology Acceptance Model to E-learning Assessment (Kelase) in Agricultural Technology Education, UniversitasNegeri Makassar

Abstract: Kelase is an E-learning program that has been applied in the Agricultural Technology Education (PTP), especially in the Toxicology and Food Safety courses. This study aims to analyze application and acceptance of PTP students to Kelase, as well as variable correlation and linearity used in the Technology Accepted Model (TAM) method. The independent variables in this study consisted of variables perceived ease of use and perceived usefulness, while the observation variable was acceptance. Techniques for collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In this study, hypothesis testing is performed using a significance level of 5% and a confidence level of 95%. According to (Feng et al, 2017;Magdalena & Dharmanto, 2020;Sukainah et al, 2019) hypothesis testing is carried out using the following formula. 𝑇 𝑡𝑎𝑏𝑒𝑙 = 𝑡(α/2; 𝑛 − 𝑘 − 1) Information: t = t table value α = error rate n = number of samples k = independent variable Determination of t table using formula (7).…”
Section: A T-testmentioning
confidence: 99%
“…In this study, hypothesis testing is performed using a significance level of 5% and a confidence level of 95%. According to (Feng et al, 2017;Magdalena & Dharmanto, 2020;Sukainah et al, 2019) hypothesis testing is carried out using the following formula. 𝑇 𝑡𝑎𝑏𝑒𝑙 = 𝑡(α/2; 𝑛 − 𝑘 − 1) Information: t = t table value α = error rate n = number of samples k = independent variable Determination of t table using formula (7).…”
Section: A T-testmentioning
confidence: 99%
“…The indicators are preferring Islamic banks, informing others about savings products (colleagues, relatives/family, and relations), not preferring savings products other than those from Islamic banks, and intending to continue saving in Islamic banks despite the lower profit sharing when compared to conventional bank interest. Perceived ease of use can be identified as the ease to learn, use, and understanding (Sukainah et al, 2019). The influence of family or friends using Islamic bank products, or the role of family or friends in choosing Islamic bank products in the form of information and encouragement from family or friends, is referred to as social influence (Rangkuti & Sulistyawati, 2014).…”
Section: Variable Measurementmentioning
confidence: 99%
“…It is intended as an educational institution social network. It is available in the form of an android application, and can also be accessed using internet browsers so that it can be accessed anytime and anywhere [3].…”
Section: Introductionmentioning
confidence: 99%
“…By using the Technology Acceptance Model (TAM) measurements, Sukainah, et al reported that students of a university in Makassar who utilized Kelase, accept it at a very high level of acceptance [3]. In another hand, Zhang, et al who questioned whether e-learning can replace classroom learning, found that e-learning has several disadvantages, such as lack of immediate feedback in asynchronous e-learning, increased preparation time for the instructor, not comfortable to some people, and potentially more frustration, anxiety, and confusion [7].…”
Section: Introductionmentioning
confidence: 99%